Kinerja Pemerintahan Desa (Studi terhadap Pembangunan Infrastruktur Jalan di Desa Turu Cinnae) - Hamzah, Muhammad Akbar; Ariana, Ariana (Universitas Indo Global Mandiri, 2024)
This research discusses the performance of the village government with an emphasis on road infrastructure development in Turu Cinnae Village, Lamuru District, Bone Regency. The aim of this research is to understand the political dynamics of the performance of improving road infrastructure development in Turu Cinnae Village and identify factors that hinder the development of this infrastructure. This research adopts a qualitative descriptive method by collecting primary data through observation, interviews and documentation, as well as secondary data from literature reviews such as books, journals, annual reports and related websites. The results of the study show that the performance of village heads in road infrastructure development is still lacking. optimal, as evidenced by the many complaints from the local community. Disincentives include the lack of attention from the village bureaucracy, the poor health of village leaders, and the reluctance of the community to donate land for road construction or rehabilitation. On the other hand, community enthusiasm to support the implementation of infrastructure development is an important supporting factor.